THE RELATIONSHIP TIME DRINKING TABLETS OF IRON AND THE EVENT OF ANEMIA PREGNANT WOMAN IN MEKAR WANGI PUSKESMAS, BOGOR CITY: HUBUNGAN WAKTU MINUM TABLET ZAT BESI DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS MEKAR WANGI KOTA BOGORâ€ - Dewi Nopitasari, Dewi (Jurnal Ilmiah Wijaya, 2019)
Based on the results of basic health research (RISKESDAS) in 2013, pregnant women who experienced anemia throughout the world amounted to 41,8%. While the prevalance of anemia in pregnant women in indonesia is 37,1%. Half of the causes of anemia are iron deficiency. In bogor city mothers who die of cuses that are related to pregnancy birth and postpartum period in 2013 were reported as 13 people. Find out the relationship between taking iron tablets with the incidence of anemia in pregnant women in the public health center blooming fragrant in bogor city in 2018-2019. This type of research is a quantitative analytic method with a cross sectional design. This research was conducted at the public health center blooming in bogor city in 2018-2019, totaling 61 respondents. Using total samping technique. The instrument used is a questionnaire when taking iron tablets and hemoglobin (HB) results for pregnant women. While the data analysis technique uses univariate and bivariate analysis. In a statistical test the study of the relationship between the time to take iron tablets and the incidence of anemia in pregnant women at the public health center blooming in bogor city in 2018-2019 can be concluded that there are 8 (13,11%) pregnant women with normal hemoglobin levels with morning drinking day, there were 28 (45,9%) pregnant women with normal hemoglobin levels with night time drinking, there were 12 (19,67%) pregnant women with mild anemia with morning drinking time, there were 7 (11,47%) mothers pregnant with mild anemia with night time drinking, there are 4 (6,56%) pregnant women with moderate anemia with morning drinking time, there are 2 (3,27%) pregnant women with moderate anemia with night time drinking Based on the chi-square statistical test, the p-vlue 0,004 ?0,05 can be concluded that it can be concluded that Ho is rejected and Ha is accepted so that there is a correlation between the time to take iron tablets and the incidence of anemia in pregnant women in bogor city